2008
DOI: 10.1002/aoc.1340
|View full text |Cite
|
Sign up to set email alerts
|

Efficient homocoupling reactions of halide compounds catalyzed by manganese (II) chloride

Abstract: A new efficient homocoupling reaction was reported in one pot by a combination of metallic magnesium and a catalytic amount of manganese (II) chloride. Various aromatic and alkyl halides underwent homocoupling smoothly, affording the corresponding symmetrical homocoupling compounds in moderate to good yields. The readily available MnCl 2 , the mild reaction conditions and the operational simplicity and practicability allow for an easy and practical procedure for the purpose of carbon-carbon bond formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 23 publications
(15 reference statements)
2
17
0
Order By: Relevance
“…[1][2][3] The discoveryo ft he biological actions of dihydrostilbenoids, such as those of the combretastatin series, [4] have sparkedr enewed research interest in the synthesis of bibenzyl derivatives. The catalytic mechanism involves the oxidative addition of benzyl halides into low-valent complexes of Mn, [8,14,[25][26][27] Fe, [9,10,28] Ni, [20,22,29] Cu, [16-18, 30, 31] V, [32] Rh, [33] In, [34] Ti, [15,35] and Sm [36,37] that can be generated in the presence of electrons ourcesw ith very negative oxidationp otentials. To expand syntheticr outes to bibenzyls, novel methods that promote the Csp 3 -Csp 3 coupling of halomethyl arenes have been developed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] The discoveryo ft he biological actions of dihydrostilbenoids, such as those of the combretastatin series, [4] have sparkedr enewed research interest in the synthesis of bibenzyl derivatives. The catalytic mechanism involves the oxidative addition of benzyl halides into low-valent complexes of Mn, [8,14,[25][26][27] Fe, [9,10,28] Ni, [20,22,29] Cu, [16-18, 30, 31] V, [32] Rh, [33] In, [34] Ti, [15,35] and Sm [36,37] that can be generated in the presence of electrons ourcesw ith very negative oxidationp otentials. To expand syntheticr outes to bibenzyls, novel methods that promote the Csp 3 -Csp 3 coupling of halomethyl arenes have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…[5] However,t his method requires stoichiometric use of excessive reducing reagents, such as Li, [6,7] Mg, [8][9][10][11][12][13][14] Mn, [15,16] Fe, [17,18] Ni, [19] andZ n [20][21][22][23][24] metals, and this limits its syntheticu tility.T he recently developed methods of transition-metal-catalyzed Csp 3 -Csp 3 coupling enable increasedc ontrol over the reaction conditions. The catalytic mechanism involves the oxidative addition of benzyl halides into low-valent complexes of Mn, [8,14,[25][26][27] Fe, [9,10,28] Ni, [20,22,29] Cu, [16-18, 30, 31] V, [32] Rh, [33] In, [34] Ti, [15,35] and Sm [36,37] that can be generated in the presence of electrons ourcesw ith very negative oxidationp otentials. For instance, Zn metal is required to promotet he oxidative additiono fb enzylb romidesi nto aN i complex with at ridentate 2,6-bisoxazolylpyridine ligand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples employ manganese (II) as the catalyst18–25 and recently Cahiez found that organomanganese reagents could be cross‐coupled with ortho ‐acylated aryl chlorides in good yields 26. Recently we reported the homocoupling reaction of halide compounds in one pot by a combination of metallic magnesium and MnCl 2 27. Herein, we report an efficient tandem cross‐coupling reaction of o ‐chlorobenzoyl chloride with dialkyl and diaryl magnesium compounds in the presence of manganese (II) chloride.…”
Section: Introductionmentioning
confidence: 95%
“…Hoffman determined the stereochemistry of the transmetalation of Grignard reagents to manganese (II) [35]. Recently, Yuan developed the manganese-catalyzed homo-coupling reaction of aliphatic halides in the presence of magnesium [36]. Although these newly developed methods are good for the preparation of biaryls, their use have been restricted to aryl bromides and iodides as starting material which somewhat limits their use due to cost and availability of starting material.…”
Section: Introductionmentioning
confidence: 99%